PENGARUH INTENSITAS MEMBACA INFORMASI WEBSITE OMBUDSMAN REPUBLIK INDONESIA (OMBUDSMAN.GO.ID) DAN PERSPEKTIF PENYANDANG DISABILITAS DI ROEMAH DIFABEL SEMARANG TERHADAP PEMAHAMAN PENYANDANG DISABILITAS TERKAIT KEBERADAAN OMBUDSMAN SEBAGAI LEMBAGA PENGAWAS PELAYANAN PUBLIK YANG PEDULI PENYANDANG DISABILITAS - Galuh Gunita Pangastuti; Adi Nugroho (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
The Ombudsman as a supervisory agency for the delivery of public services uses the website as a medium of information. Currently, it is still rare to find public service facilities that are friendly to persons with disabilities, this can be seen from several news reports in online mass media that report persons with disabilities do not receive special attention in public services. This type of research is a quantitative explanatory study and uses the media effects theory and sense making theory. The test results show that the R Square value is 0.521 or 52.1%. This means that 52.1% understanding of persons with disabilities about the existence of the Ombudsman as a public service supervisory agency that cares for persons with disabilities can be explained by the intensity of reading the ombudsman.go.id website. While the rest (100% -52.1% = 47.9%) was explained by other factors. From the test results obtained that the value of R Square is 0.394 or 39.4%. This means that 39.4% understanding of persons with disabilities about the existence of the Ombudsman as a public service supervisory agency that cares for persons with disabilities can be explained by the intensity of reading the ombudsman.go.id website. While the rest (100% -39.4% = 60.6%) is explained by other factors. This means that if the intensity of reading the website and the perspective of persons with disabilities are increased together towards a positive direction, the understanding of people with disabilities about the existence of the Ombudsman as a public service supervisory agency that cares for people with disabilities. The sample in this study was 70 members of the Roemah Difabel Semarang foundation who read information through the ombudsman website. go.id related to the Ombudsman as a public service supervisory agency that cares for persons with disabilities and knows the facts of public services that are not in accordance with standards for persons with disabilities.